Rewrite the given function so that we can proceed with the power rule instead of the quotient rule.

`f(t)=2-4t^(-1)`

Take the derivative of the given function. The derivative of a constant is zero.

`f'(t) = 4t^(-2) = 4/t^2`

Substitute `(t,f(t)) = (4,1)` .

`f'(4)=4/(4^2) = 4/16 = 1/4`

The derivative,...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

Rewrite the given function so that we can proceed with the power rule instead of the quotient rule.

`f(t)=2-4t^(-1)`

Take the derivative of the given function. The derivative of a constant is zero.

`f'(t) = 4t^(-2) = 4/t^2`

Substitute `(t,f(t)) = (4,1)` .

`f'(4)=4/(4^2) = 4/16 = 1/4`

The derivative, or the slope, at the point is one-fourth.

Graph the derivative function and check the value at t=4. It appears to be about 1/4.